Quiet eye duration and gun motion in elite shotgun shooting - Causer, J.; Bennett, S. J.; Holmes, P. S.; Janelle, C. M.; Williams, A. M. (Medicine & Science in Sports & Exercise, 2010)
Introduction: No literature exists to document skill-related differences in shotgun shooting and whether these may be a function of eye movements and control of gun motion. We therefore conducted an exploratory investigation of the visual search behaviors and gun barrel kinematics used by elite and subelite shooters across the three shotgun shooting subdisciplines.